Islam sebagai Agama Wahyu, Pemikiran dan Peradaban - Marini, Melani Ida; Istikotimah, Istikotimah; Jauhara, Ratna; Mujiburrohman, Mujiburrohman (Lembaga Yasin AlSys, 2026)
Islam and civilization constitute an inseparable unity, as from its very emergence Islam has brought a civilizational concept and mission rooted in dîn (religion) grounded in divine revelation, so that Islamic civilization is known as tamaddun or madaniyyah. Building on this view, this article aims to explicate in detail the meaning and concept of civilization, to compare Western and Islamic civilizations, and to explain the nature of Islam as religion, revelation, thought, and civilization on the basis of reliable historical evidence. The study employs a qualitative descriptive method grounded in literature review and philosophical–historical analysis of key civilizational concepts within both Western and Islamic traditions. The findings show that Islamic civilization is rooted in revelation and historically embodied, among others, through the experience of Madinah as the initial locus for articulating Islamic tamaddun, whereas modern Western civilization tends to be built upon the centrality of human reason and subjectivity, giving rise to the dominance of a secular–cognitive civilization. This comparative analysis underscores the fundamental distinctions between the two, while simultaneously offering a critique of the hegemony of modern Western civilization that tends to neglect the dimensions of revelation and transcendence. The study concludes that, from an Islamic perspective, human reason and intellect should ideally operate in harmony with revelation, and that Islam has historically shaped world civilization for centuries, thereby offering an alternative paradigm for developing a civilization that more evenly balances spiritual, moral, and rational dimensions.